(3GdaGUd Hjf GdQGhi hGdhGYis - (3Hf NdGO , GdMSf Hf YHO GdQMef Hf NdGO GdQGegQeRj, CHh eMeO,J (B360 (3g` s
(3ChdgG (B:s
(3GdMeO ddg hdG Edg EdG Gddg EYJQVJ WGFaI eef jTfC GdMOjK hjHZV Cgdg , abGdhG HJNajV CUMGH GdMOjK s
(3BNQgG (B:s
(3Yf CfS Hf eGdc bGd bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3dHjc MLkG MbkG , JYHOkG hQbkG BNQ GdLRA GdSGHY ef GdaGUd , hHJeGeg Je LejY GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B194 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B235s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ GdZQHjI (B(19) s
Keywords: (3GdMOjK h GdeUWdMs